A flexible phase change organohydrogel created using Pickering emulsion technology for thermoelectric conversion and temperature sensing. Issue 36 (30th August 2022) - He, Yingying; Wei, Yuan; Qian, Yangyang; Wang, Chunyu; Liu, Yijun; Ye, Zhixin; Chen, Gang
Abstract : A flexible phase change organohydrogel was prepared using Pickering emulsion technology, exhibiting great potential for thermosensitivity, waste heat harvesting and green energy production. Abstract : Integration of thermoelectric generators with phase change materials (PCMs) is expected to be a promising technology for harvesting and converting waste heat to electricity, thus alleviating energy shortage and ecological damage. However, the low output electricity and inherent hardness of PCMs have limited their wide application. Herein, a multifunctional phase-change organohydrogel filled with paraffin wax (PW) microspheres is prepared using Pickering emulsion technology and UV-initiated polymerization. The PW was encapsulated in cellulose nanofibril (CNF)–MXene–Fe3 O4 hybrid shells and then inlaid into a flexible polyacrylamide (PAAm) matrix. This unique structural feature provides enhanced thermoelectric conversion, superior shape stability, and excellent mechanical properties. The resultant organohydrogel can continuously harvest waste heat, transfer it into a thermoelectric generation system, and output electrical energy. The generated output voltage and power can reach 627.0 mV and 65.7 mW, respectively. The thermoelectric generator also exhibited good thermal cycling stability (for more than 50 cycles). Besides, the composite organohydrogel possesses satisfactory thermosensing capacity to monitor real-time temperature variation and hot steam behavior. This work opens up opportunities for highly efficient conversion of waste heat to electricity.